Long-Term Remission of a Spinal Atypical Teratoid Rhabdoid Tumor in Response to Intensive Multimodal Therapy - Fahd Refai; Haneen Al-Maghrabi; Hassan Al Trabolsi; Jaudah Al-Maghrabi (Case Reports in Pediatrics)
Atypical teratoid rhabdoid tumors (ATRTs) are rare and aggressive central nervous system tumors that infrequently arise in spinal locations in young children. Provided clinical and diagnostic suspicion is high, the histopathological diagnosis is relatively straightforward to secure by testing for the characteristic loss of the tumor suppressor protein SMARCB1/INI1. Here, we describe a case of thoracic spinal ATRT in a three-year-old boy that showed characteristic aggressive progression until managed with intensive multimodal therapy to achieve durable long-term remission. In doing so, we review the histopathological features, management, and current advances in molecular biology that hold promise for personalized ATRT therapy.